Pereira Suture: an Alternative Compression Suture to Treat Uterine Atony - Agung B Setiyono; Alamsyah Aziz; Agus Sulistyono; Johanes C Mose (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To evaluate the use of Pereira suture as a conservative surgical management in postpartum hemorrhage due to uterine atony. Methods: The study was performed in the Department of Obstetrics and Gynecology, Temanggung General Hospital, Central Java, Indonesia. Data was retrieved retrospectively from medical records, from January 2011 until December 2013. Results: Pereira suture was done in four cases of uterine atony with failed conservative management, and the procedure was found to be successful in all cases. Conclusion: Pereira suture is an alternative surgical procedure for the treatment of uterine atony after failed conservative management. [Indones J Obstet Gynecol 2015; 3: 177-182] Keywords: pereira suture, postpartum hemorrhage, uterine atony